A genomic screen for angiosuppressor genes in the tumor endothelium identifies a multifaceted angiostatic role for bromodomain containing 7 (BRD7) - van Beijnum, Judy R. (Angiogenesis, 2017)
Tumor angiogenesis is characterized by deregulated gene expression in endothelial cells (EC). While studies until now have mainly focused on overexpressed genes in tumor endothelium, we here describe the identification of transcripts that are repressed in tumor endothelium and thus have potential suppressive effects on angiogenesis. We identified nineteen putative angiosuppressor genes, one of them being bromodomain containing 7 (BRD7), a gene that has been assigned tumor suppressor properties. BRD7 was studied in more detail, and we demonstrate that BRD7 expression is inversely related to EC activation. Ectopic expression of BRD7 resulted in a dramatic reduction of EC proliferation and viability. Furthermore, overexpression of BRD7 resulted in a bromodomain-dependent induction of NFκB-activity and NFκB-dependent gene expression, including ICAM1, enabling leukocyte–endothelial interactions. In silico functional annotation analysis of genome-wide expression data on BRD7 knockdown and overexpression revealed that the transcriptional signature of low BRD7 expressing cells is associated with increased angiogenesis (a.o. upregulation of angiopoietin-2, VEGF receptor-1 and neuropilin-1), cytokine activity (a.o. upregulation of CXCL1 and CXCL6), and a reduction of immune surveillance (TNF-α, NFκB, ICAM1). Thus, combining in silico and in vitro data reveals multiple pathways of angiosuppressor and anti-tumor activities of BRD7. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s10456-017-9576-3) contains supplementary material, which is available to authorized users.